2013
DOI: 10.1063/1.4795543
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastrong light-matter coupling at terahertz frequencies with split ring resonators and inter-Landau level transitions

Abstract: Articles you may be interested inTerahertz response of fractal meta-atoms based on concentric rectangular square resonators J. Appl. Phys. 118, 193103 (2015) We study strong light-matter coupling at terahertz frequencies employing a system based on an array of deeply subwavelength split ring resonators deposited on top of an ensemble of modulation-doped quantum wells. By applying a magnetic field parallel to the epitaxial growth axis, at low temperatures, Landau Levels are formed. We probe the interaction of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 28 publications
4
28
0
Order By: Relevance
“…This provides a linear tuning of the cyclotron energy. With such an experimental arrangement we have observed three absorption features [17,18]: two are related to the lightmatter coupled system and the third middle peak is the cyclotron signal coming from the material which lies in between the resonators. This cyclotron signal is only weakly coupled to the metasurface and follows the expected linear dispersion for a cyclotron transition ω = * c eB m   .…”
Section: The Metamaterials Cavity: Fabrication Experimental Results mentioning
confidence: 99%
See 1 more Smart Citation
“…This provides a linear tuning of the cyclotron energy. With such an experimental arrangement we have observed three absorption features [17,18]: two are related to the lightmatter coupled system and the third middle peak is the cyclotron signal coming from the material which lies in between the resonators. This cyclotron signal is only weakly coupled to the metasurface and follows the expected linear dispersion for a cyclotron transition ω = * c eB m   .…”
Section: The Metamaterials Cavity: Fabrication Experimental Results mentioning
confidence: 99%
“…We recently demonstrated that the cyclotron transition of a 2-dimensional electron gas (2DEG) coupled to a metasurface of subwavelength split-ring resonators can attain the ultrastrong coupling regime showing record high values of the normalized light-matter coupling ratio = Ω ω 0.58 c [17,18]. As discussed in the introduction of the work of Hagenmüller et al [14], starting from the constitutive relation Ω = × × d E N vac  and using the same symbols it can be shown that the normalized light-matter coupling ratio Ω ω c for this cyclotron-based system scales in the following way with the relevant physical parameters:…”
mentioning
confidence: 99%
“…This has led to the demonstration of light-matter coupling with a number of quantum systems including phonons, 12 intersubband transitions (ISBTs) in quantum wells (QWs), 13,14 vibrational modes of molecules, 15 and cyclotron resonances. 16,17 The coupling of MMs to ISBTs in QWs is especially appealing for applications due to the tunability of the transition frequency, the large dipole moment, and the possibility of optical and/or electrical modulation. 18 However, the experimental demonstration of ultrastrong light-matter coupling in such a system is still open.…”
mentioning
confidence: 99%
“…Recently, ultrastrong coupling experiments have been performed, where the cyclotron resonance of the two dimensional electron gas (2DEG) is coupled to THz MM resonators1617181920. The transitions between the Landau levels are brought into resonance with the MMs by tuning the magnetic field.…”
mentioning
confidence: 99%